"Nóis somo irmão congueiro": estudo sobre congadas no século XXI em São Paulo - Munhoz, Vanessa (2006)
This dissertation object is the cultural practice generically known as congada , comprehended here as popular Afro-Brazilian culture. The historic origin of this practice is related to the celebrations parades that used to take place when African kings were crowned in Brazil. Under the slavery system, the royal couple was selected among black brotherhoods. Many groups and communities still celebrate their ancestral past through the congada , a space to build and strengthen their social-cultural links, identity reconstruction and devotion. This research was developed around existing congada groups in the state of São Paulo. Through qualitative techniques, five groups were studied using a participating observation approach and life histories of their leaders were collected based on memory framework. The work is driven by the leader Silvio Antonio de Oliveira trajectory, who is still ahead of the only guard existing these days in the city of São Paulo. The main point raised in this research is the real meaning of being a congada membership, in Sao Paulo, nowadays. In other words, this paper tries to understand how this practice makes sense to the congueiros , how they reinvent their cultural repertory talking to other repertories and also how they rebuild their identities based on the collective memory